1999
DOI: 10.1093/ajcn/69.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments in energy expenditure and substrate utilization during late pregnancy and lactation

Abstract: Background: Metabolic adjustments occur during pregnancy and lactation to support fetal growth and milk synthesis; however, the effect of body composition and hormonal milieu on these changes is poorly understood. Objective: We hypothesized that energy metabolism changes during pregnancy and lactation to support fetal growth and milk synthesis, and that body composition and hormonal milieu influence these alterations. Design: We measured energy expenditure, body composition, and hormone, metabolite, and catech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
167
5
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(183 citation statements)
references
References 34 publications
9
167
5
2
Order By: Relevance
“…These results are similar to those found in a study of Guatemalan women (Schutz et al, 1980) using the HR method, as well as those found in studies of Swedish (Forsum et al, 1992). North American (Butte et al, 1999), and Gambian women (Singh et al, 1989) using the doubly labeled water method.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are similar to those found in a study of Guatemalan women (Schutz et al, 1980) using the HR method, as well as those found in studies of Swedish (Forsum et al, 1992). North American (Butte et al, 1999), and Gambian women (Singh et al, 1989) using the doubly labeled water method.…”
Section: Discussionsupporting
confidence: 90%
“…Butte et al, (1999) did, however, report a significantly higher fasting basal respiratory exchange ratio, which they assumed to be linked to the preferential use of glucose by the mammary gland for synthesis of the carbohydrate and protein components of milk.…”
Section: Discussionmentioning
confidence: 93%
“…Some authors have found a decrease in BMR during lactation (Butte et al, 1997) or during seasonal food shortage (Ategbo et al, 1995) in malnourished women (Ferro-Luzzi et al, 1997), but the apparent decrease disappeared when adjustment was made for body composition. Recent studies have described an enhanced carbohydrate utilization (Butte et al, 1999) and a 5% increase in muscular ef®ciency during lactation (Spurr et al, 1998). The present study was not able to address adaptive effects in relation to lactation.…”
Section: Energy Balance In Lactating Bangladeshi Women S Vinoy Et Almentioning
confidence: 80%
“…Some studies have found a weight loss, corresponding to a fat mass reduction (Forsum et al, 1992;Motil et al, 1998;Butte et al, 1999), and others no change (van Raaij et al, 1990;Goldberg et al, 1991;Lovelady et al, 1995), because of increased energy intake to compensate for lactation. In the present study the women lost weight between 3.5 and 5.5 months postpartum, most of which was fat-free mass, but there was also a reduction in suprailiac skinfold thicknesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation